(untitled) (Journal of the College of Basic Education, 2024)
The novel “Noor Khidr Khan” by the novelist “Jaber Khalifa Jaber” belongs to the visual narrative experience, which is distinguished by its search for roots and originality on the one hand, and its aspiration for experimentation and following the waves of modernization in writing. This research looks forward to an interpretive reading of the novel according to the approach of the French thinker, “Paul Ricoeur,” who made the tireless effort to study The aspects of the relationship between historical narrative and the fictional imagination, his theorization of narrative identity in literary discourses, and the importance he gave to the system of interweaving as a regularity of historical trouble in the process of temporality. The study is concerned with all that was mentioned.